Réponses

2013-11-16T22:53:38+01:00
1) développé
16x^{2}+8x+1+8x^{2}+24x+2x-6\\ \\ 24x^{2}+34x-5

2) Factoriser
(4x+1)(4x+1+2x-6)\\ \\ 
(4x+1)(6x-5)

3)
(4x+1)(6x-5)=24x^{2}-14x-5\\ \\ \Delta=b^{2}-4ac\\ \\ \Delta=-14^{2}-4*24*(-5)\\ \\ \Delta=676\\ \\x= \frac{-b\pm \sqrt{\Delta} }{2a} \\ \\ x= \frac{14\pm \sqrt{676} }{48} \\ \\ x= \frac{-14\pm 26}{48}\\ \\  x_{1} = \frac{5}{6} \ \ \ \ \ \ \x x_{2} =- \frac{1}{4}
4)
A(0)=(4(0)+1)^{2}+(4(0)+1)(2(0)-6)\\ \\ A(0)=1+1*(-5)\\\\ A(0)=-5\\\\A(-1)=(4(1)+1)^{2}+(4(1)+1)(2(1)-6)\\ \\ A(-1)=9+(-3)*(-11)\\\\ A(-1)=42\\\\A(\frac{5}{6})=(4(\frac{5}{6})+1)^{2}+(4(\frac{5}{6})+1)(2( \frac{5}{6} )-6)\\ \\ A(\frac{5}{6})=(4(\frac{5}{6})+1)^{2}*0\\\\ A(\frac{5}{6})=0
Je ne peux plus edité mais pour la factorisation tu obtien
obtiens (4x+1)(4x+1+2x-6)= (4x+1)(6x-5)